Synergistic Effects of 4-Aminopyridine and Paclitaxel on MCF 7 Cell Line - GARİP, GÜNSELİ AYŞE (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objectives: Aim of this study is to increase the effectiveness of paclitaxel (PTX) with the use of 4 - aminopyridine (4-AP) on breast cancer cell line MCF-7. Methods: In this study, L-929 (ATCC CRL-6364) and MCF-7 (ATCC - HTB 22) cell lines were used. IC50 and survival values were determined by trypan blue exclusion; cell cycle analysis was determined by measuring levels of Cdk2 and Histone (H3) and plasma membrane potential (Vm) measurements were performed using fluorescent Bis-(1,3-dibutylbarbituric acid) trimethine oxonol (DiBaC4(3)). Results: IC50 values were determined for two agents and these values were combined. Combination treatments ie. 4-AP (4 mM) + PTX (5 nM) and 4-AP (4 mM) + PTX (7.5 nM) decreased viability 17% +/- 8.08 and 45% +/- 3.18, respectively for L-929 cells and decreased viability 60%+/- 3.7 and 74%+/- 2.6, respectively for MCF-7 cells. For L-929 cells, plasma membrane potential measurements resulted in depolarization for 4-AP, PTX (5 nM) and PTX (7.5 nM), and resulted in hyperpolarization for the combinations. For MCF-7 cells, plasma membrane potential measurements resulted in depolarization for 4-AP, PTX (7.5 nM) and 4-AP + PTX (5 nM), and resulted in hyperpolarization for PTX (5 nM) and 4-AP + PTX (7.5 nM). Changes of Cdk2 and H3 levels showed mostly G1 arrest for MCF-7 cells and G2/M arrest for L-929 cells. Conclusions: Combination treatments increased the cell death for MCF-7 cells. But, combination treatments didn't show synergistic effect on L-929 which is accepted as a non-cancerous cell. These data showed that use of 4-AP in combination with the anticancer agent paclitaxel is a promising approach for cancer treatment.
Keywords: 4 - aminopyridine; paclitaxel; MCF-7 breast cancer cell line; POTASSIUM CHANNELS; BREAST-CANCER; TAXOL; APOPTOSIS